A cost-effective isogeometric approach for composite plates based on a stress recovery procedure. (1st April 2018) - Dufour, John-Eric; Antolin, Pablo; Sangalli, Giancarlo; Auricchio, Ferdinando; Reali, Alessandro
Abstract: This paper introduces a cost-effective strategy to simulate the behavior of laminated plates by means of isogeometric 3D solid elements. Exploiting the high continuity of spline functions and their properties, a proper out-of-plane stress state is recovered from a coarse displacement solution using a post-processing step based on the enforcement of equilibrium in strong form. Appealing results are obtained and the method is shown to be particularly effective on slender composite stacks with a large number of layers. These are indeed the cases where traditional (e.g., "layerwise") approaches are more computationally heavy and where researchers are more inclined to look for alternatives, making the proposed method a very attractive solution.